(untitled) (Journal of Governance and Development (JGD), 2023)
The evolution of the Chinese business activities in several Southeast Asian (SEA) countries such as Indonesia, The Philippines, Thailand, and Malaysia is rather difficult to separate from the influence of the state policies and the behavior of political elites. In Indonesia, the relationship of the Chinese businessmen, particularly in big business activities with Suharto regime, known as ‘Orde Baru’ (New Order), shows a model of patron-client behavior and crony capitalism networks. The accommodation, protection, and access provided by the regime has led to the economic capitalization of the Chinese business in Indonesia. In fact, the relationship between Chinese business and New Order’s regime is mutually beneficial and very tight. After the fall of the New Order regime in 1998, the political system in Indonesia became more open and decentralized (locally known as ‘Otonomi Daerah’ or Regional Autonomy). This shows the important role of the local government in making decision particularly in terms of economy sector and infrastructure development’s project. The paper aims at three folds: first is to discuss the pattern of the Chinese ethnic business activities in post-New Order regime and its impact to the local development. Second, to discuss to what extent the Chinese business practice particularly in real-estate or property sector influenced by the local elites behavior. Third is to discuss whether the patron-client relationship and crony capitalism behavior in the local context between Chinese businessmen with local elite occurred as in the Suharto’s era or not. The findings show that the pattern of the Chinese business in post-Suharto’s Indonesia in several business sectors (medium and mediumlarge businesses) sometimes still rely on the use of networks with local elites. The local government faced a ‘complex dilemma’ in term of development projects, where basically requires substantial capital from big companies, then they often violated the laws to accelerate the development projects. The patron-client networks and crony capitalism vaguely occurred among the Chinese businessmen and local elite. However, the level of their closeness is not too visible as in the Suharto’s era. In other circumstances, the Chinese businessmen also become superior actors, while the local elites only become inferior actor, because the companies actually seemed to be able to control the government decision indirectly.